2010
DOI: 10.1124/jpet.110.172932
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Detection and Time Course of Cerebral Microhemorrhages during Passive Immunotherapy in Living Amyloid Precursor Protein Transgenic Mice

Abstract: In recent years immunotherapy-based approaches for treating Alzheimer's disease have become the subject of intensive research. However, an important mechanistic-related safety concern is exacerbation of the risk of microhemorrhage that may be associated with fast removal of amyloid-␤ (A␤) deposits found in blood vessels or brain parenchyma. Rapid in vivo detection of microhemorrhages in living amyloid precursor protein transgenic mice has not been described, and histological analysis can take several months be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
(71 reference statements)
2
17
0
Order By: Relevance
“…As previously reported 3335 , on non-stained MRI, microhemorrhages were visible as rare hypointense spots (Fig. 7F,G).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As previously reported 3335 , on non-stained MRI, microhemorrhages were visible as rare hypointense spots (Fig. 7F,G).…”
Section: Resultssupporting
confidence: 85%
“…Microhemorrhages are often associated with aging and amyloid pathology in mice and in humans 32 . These lesions are hypointense on MR images 3335 , and could thus be misinterpreted as amyloid plaques on Gd-stained MR images. We showed that large microbleeds are distinguishable from amyloid plaques based on their superior size.…”
Section: Discussionmentioning
confidence: 99%
“…Along the same line, Dickstein et al (2006) demonstrated that Aβ immunization therapy could restore BBB integrity in the same AD mouse model (Tg2576), in addition to improvement of typical AD brain pathological features such as plaque burden and microgliosis, suggesting a new strategy for AD treatment focusing on BBB function (Dickstein et al, 2006). However, we need to give careful consideration to the effect of Aβ immunization on BBB function because it has also been demonstrated that passive immunization with Aβ antibodies resulted in a significant increase in both the frequency and severity of CAA-related microhemorrhages in different APP transgenic mouse models (Pfeifer et al, 2002; Racke et al, 2005; Burbach et al, 2007; Luo et al, 2010). …”
Section: Bbb Function In Alzheimer Brainmentioning
confidence: 99%
“…Histological analyses demonstrated an increased number of CAA vessels and of iron loaded macrophages in the vicinity of CAA vessels, for mice receiving the β 1 antibody. In addition, a study using T * 2 -weighted MRI for the detection of CMBs in Tg2576 mice treated with either a non-selective antibody (6G1) targeting soluble and insoluble Aβ or a more selective antibody (8F5) targeting primarily soluble Aβ (Luo et al, 2010). Both antibodies increased CMB incidence in aged APP transgenic mice compared with baseline or vehicle treatment.…”
Section: Assessing the Effects Of Therapies Targeting Vascular Patholmentioning
confidence: 99%